The reconstruction of women's dignity in the age of social media: A discourse on the subject of cancel culture and the illusion of gender solidarity - Nur Sitha Afrilia (Priviet Social Sciences Journal, 2026)
The emergence of cancel culture has transformed digital spaces into arenas of moral judgment, where public outrage frequently functions as a mechanism of social control. In the Indonesian context, this phenomenon unveils pronounced gender asymmetries, particularly in the form of symbolic punishment endured by women, which is disproportionate and enduring. This study aims to examine how cancel culture functions as a gendered practice that undermines women's dignity and reframes solidarity through conditional moral standards. Employing a virtual ethnography approach, this study analyzes digital interactions, public narratives, and mediated responses surrounding selected cases of online cancellation involving women. The findings suggest that cancel culture functions not merely as an expression of collective accountability; rather, it constitutes a structured process shaped by patriarchal moral hierarchies, algorithmic amplification, and selective public empathy. Women's purported moral transgressions are characterized as character flaws, whereas analogous actions by men are frequently contextualized and pardoned. In addition, the discourse of Woman Supporting Woman frequently functions as a normative instrument that disciplines women rather than cultivating authentic solidarity. This study makes a significant contribution to contemporary feminist and communication scholarship by conceptualizing cancel culture as a form of gendered power practice and emphasizing the need to reposition digital solidarity as a structural, ethical, and political commitment to achieving gender justice.